Effect of chitosan on distearoylphosphatidylglycerol films at air/water and liquid/liquid interfaces - Cámara, Candelaria Inés (2013)
The effect of chitosan on distearoylphosphatidylglycerol (DSPG) films was analyzed by cyclic voltammetry, surface pressure-area and surface potential-area isotherm and Brewster Angle Microscopy. Experiments of cyclic voltammetry at a liquid/liquid interface demonstrated a blocking effect of DSPG to tetraethylammonium (TEA+) cation transfer from the aqueous to the organic phase. This effect was reversed by the presence of chitosan, which modifies the film structure. Special emphasis was placed on the nature of the supporting aqueous electrolyte (LiCl or CaCl2). In the presence of LiCl the permeability of the film increases when chitosan is present in the aqueous phase, minimizing the blocking effect of the film on TEA+ transfer probably due to the presence of bare zones at the interface. Oppositely, in presence of Ca2+, the enhancement of permeability was not observed, probably due to the impediment of chitosan to penetrate into the very tightly compacted film of DSPG. Electrochemical experiments were completed with viscosity measurements to explain the variation of diffusion coefficients for TEA+. Isotherms of compression for DSPG monolayers modified with chitosan, demonstrate that this polymer produces an expansion of the DSPG film and modifies the compression factor, for both electrolytes studied. Images of Brewster angle microscopy evidence an increase in the optical thickness of the DSPG films in presence of chitosan indicating that the polymer interacts with DSPG molecules at low and high molecular areas.